1787 Measuring Exhaled Co2 During Mask Ventilation of Preterm Infants at Birth; A Novel Tool for Assessing Lung Aeration?. (October 2012) - Schmölzer, G; Kamlin, O; Davis, P; Hooper, S
Abstract : Background: Positive pressure ventilation (PPV) remains the cornerstone of respiratory support after birth. Although, gas going in and out of the lung can be measured with a respiratory function monitor, gas exchange (or effective ventilation) may only be determined by presence of exhaled CO2 . Aim: To identify non-invasive clinical tools to assess lung aeration in infants receiving PPV after birth. Methods: Deliveries of preterm infants < 32 weeks gestation were attended. During PPV we measured airway pressures, gas flow and tidal volume (VT ), exhaled CO2, heart rate and oxygen saturation. We compared delivered VT and heart rate before and after exhaled CO2 was measured. Results: In 10 preterm infants exhaled CO2 and respiratory functions were recorded; their mean (SD) birth weight and gestational age was 27 (2) weeks and 902 (287) grams, respectively. A median (IQR) of 23 (17–43) inflations was delivered with no exhaled CO2 . The median (IQR) VT when no CO2 was measured was 1.9 (1.0–3.8) mL/kg compared to 8.3 (2.1–10.3) mL/kg when exhaled CO2 was measured (p<0.0025) 1). The mean (SD) heart rate while no CO2 was exhaled was 61 (6) beats per minute compared to 104 (41) beats per minute 60 seconds after CO2 was measured. Conclusion: Delivered VT and heart rate was significantly lower when no CO2 was exhaled. The presence of exhaled CO2 was accompanied by increases in HR. Combined VT measurements, changes in heart rate and detection of exhaled CO2 may provide information on lung aeration of infants transitioning after birth.